2013
DOI: 10.5194/amtd-6-4511-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrieval of desert dust aerosol vertical profiles from IASI measurements in the TIR atmospheric window

Abstract: Desert dust aerosols are the most prominent tropospheric aerosols, playing an important role in the Earth's climate. However, their radiative forcing is currently not known with sufficient precision to even determine its sign. The sources of uncertainty are multiple, one of them being a poor characterisation of dust aerosols vertical profile on a global scale. In this work, we tackle this scientific issue by designing a method for retrieving dust aerosols vertical profiles from Thermal Infrared measurem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The overall results of AEROIASI show that the DOF or the number of independent pieces of information in the retrieval of dust profiles varies during the iterative procedure, a typical value of ~1.4 being used during the first iterations designed to determine the shape of the dust extinction profiles. This is similar to the DOF of ~1.5 obtained with the approach of Vandenbussche et al [], which also derives dust vertical profiles from IASI. In order to obtain numerically stable results, DOFs are limited to ~1 during the last iterations near convergence (using the auto‐adaptive scaling factor γ ).…”
Section: Desert Dust Observations From Aeroiasisupporting
confidence: 87%
See 3 more Smart Citations
“…The overall results of AEROIASI show that the DOF or the number of independent pieces of information in the retrieval of dust profiles varies during the iterative procedure, a typical value of ~1.4 being used during the first iterations designed to determine the shape of the dust extinction profiles. This is similar to the DOF of ~1.5 obtained with the approach of Vandenbussche et al [], which also derives dust vertical profiles from IASI. In order to obtain numerically stable results, DOFs are limited to ~1 during the last iterations near convergence (using the auto‐adaptive scaling factor γ ).…”
Section: Desert Dust Observations From Aeroiasisupporting
confidence: 87%
“…Note that we use AERONET‐derived radius and width averaged over East Asia observed during the dust outbreak case study described in section 4. According to test cases presented by Pierangelo et al [] and Vandenbussche et al [], IASI thermal infrared spectra are expected to be significantly sensitive to dust altitudes and AODs, as brightness temperatures may differ by ~10 to ~12 K (depending on wave number) both for changes in the AOD at 10 µm from 0.75 to 2.5 or in the dust altitude by 3 km. On the other hand, a lower sensitivity is found with respect to particle size, as brightness temperatures change considering two typical dust size distributions at most by ~1 K and ~2 K (both around 1100 cm −1 ) for a dust layer respectively located at 1–2 km and 4–5 km.…”
Section: Desert Dust Observations From Aeroiasimentioning
confidence: 99%
See 2 more Smart Citations
“…With an effective radius of 1.66 μm, this distribution can be considered to be a coarse mode distribution, even when most of the particles are in the accumulation mode (smaller than 1 μm). While dust particle size distributions can vary greatly in space and time (Mahowald et al, ; Reid et al, ), the effect of the size distribution on the retrieved DOD has been shown to be of second‐order importance (Capelle et al, ; Vandenbussche et al, ), and hence we have neither considered other size distributions nor attempted to retrieve an effective radius.…”
Section: Training the Nnmentioning
confidence: 99%